The impact of a school based oral hygiene instruction program on the gingival health of middle school children in Riyadh: Saudi Arabia - Hessa Alwayli; Hezekiah A Mosadomi; Essam Alhaidri (Wolters Kluwer Medknow Publications, 2015)
Aim: To determine the impact of a school-based oral hygiene instructions program on the gingival health of children in randomly selected middle schools in Riyadh, Saudi Arabia. Materials and Methods: Nine hundred and fourteen children were selected from nine schools that were randomly determined from Riyadh City public schools. After obtaining the parents' consent, the criteria-guided enrolment of study participants yielded 457 children in the control group and 457 students in the experimental group. The intervention design was 90 days experimental period with an intermediate follow-up visit at 45 days. A calibrated examiner (HW) measured the plaque index (PI) and the gingival index (GI). The indices were measured at day 1, day 45 and day 90 in both the control and the experimental groups. Results were analyzed with Wilcoxon sign rank test for each index, site, and by sessions for each group to determine if the scores had increased, decreased, or remained the same between intervals. Results: Plaque and gingival scores in the control group showed a steady improvement throughout the experimental period when compared with the baseline scores. Scores in the experimental group were significantly improved at each session between baseline and session 2 (45 days) and session 3 (90days) respectively. Conclusions: The continued reduction of GI and PI scores at the end of the intervention observed in this pilot study suggest that a school-based oral hygiene measures program can significantly improve oral health among school children in Saudi Arabia.